2014
DOI: 10.1016/j.engfailanal.2014.04.031
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic method for fault detection in wind turbine drivetrains

Abstract: In this paper, a prognostic method is presented for fault detection in gears and bearings in wind turbine drivetrains. This method is based on angular velocity measurements from the gearbox input shaft and the output to the generator, using two additional angular velocity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…The main shaft loads, or the forces and moments, are applied at the end of the main shaft where the rotor hub is connected. The NREL GRC 750-kW multibody model is built up and completed as part of the GRC project, which is verified by experiments for gearbox internal loads and employed in various earlier studies [40][41][42][43][44][45][46][47]. The bearings are modelled with linear diagonal stiffness and with clearances.…”
Section: -Model Verification: Experiments and Instrumentationmentioning
confidence: 99%
“…The main shaft loads, or the forces and moments, are applied at the end of the main shaft where the rotor hub is connected. The NREL GRC 750-kW multibody model is built up and completed as part of the GRC project, which is verified by experiments for gearbox internal loads and employed in various earlier studies [40][41][42][43][44][45][46][47]. The bearings are modelled with linear diagonal stiffness and with clearances.…”
Section: -Model Verification: Experiments and Instrumentationmentioning
confidence: 99%
“…In [11] a multibody model of the NREL GRC 750 kW gearbox is presented, with a number of faults in the gearbox. Frequency analysis are performed in this work to identify potential frequency ranges for fault detection in this gearbox, using both normal available speed measurements and as well additional speed measurements on additional stages in the gearbox.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper the frequency based detection scheme presented in [10] is applied to the data used in [11] and it is shown that faults can be detected using the rotor and generator speed measurements which are standard measurements available in wind turbine control systems.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy ballast deep in 43 the hull gives the platform its stability. In the global analysis, first order and viscous hydrodynamic 44 forces as well as mean wave drift forces were applied and Newman's approximation was used to 45 estimate the difference-frequency wave excitation.…”
mentioning
confidence: 99%
“…The MBS tool provides a powerful method for load effect analysis 161 of wind turbine drivetrains and has been successfully used in earlier studies (e.g. [5,41,42,43]). …”
mentioning
confidence: 99%